Tinjauan Ekoteologi Relasi Manusia dan Alam dalam Tradisi Sesuci Diri di Candi Jolotundo Mojokerto - Rafsanjani, Anugerah Zakya (Fakultas Ushuluddin, Adab dan Humaniora Institut Agama Islam Negeri (IAIN) Jember, 2018)
This article analyzes about relation between human and nature in the â€œself-cleansingâ€ tradition and knows the meaning of purity in the ecotourism perspective in the Seloliman village of Mojokerto. The purpose of this study is to understand human and natural relations in a tradition as self-serving and to know the meaning of self as purely in the ecotourism perspective. The results of this study concluded that, in the perspective of Javanese philosophy, a purely self-made tradition was used to draw closer to God, especially in the silent procession. The process of silence is the stage where a person performs self-reflection and reaches harmony with God and nature. In the perspective of existentialistic phenomenology, the ability to understand Jolotundo as a space for spiritual practice provides an understanding of spiritual actors in their interests in this world, and their ontological relations with nature and their world. In the ecotourism perspective, as self-serving has undergone cultural acculturation in each method and its meaning, this indicates that every religion that is acculturated in a purified tradition has a universal meaning about the existence of nature.